The Effect of Principal Transformational Leadership on Teacher Performance Mediated by Work Motivation - Doutel, Jose dos Santos; Imron, Ali; Sumarsono, Raden Bambang (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2023)
The purpose of this research is to find out and analyze the influence of the principal's transformational leadership on teacher performance mediated by work motivation. This research uses descriptive quantitative research with a correlational approach. The subjects of this research were high school teachers in Liquiça Regency. The sample in this study was 159 teachers, and it was taken using simple random sampling techniques. The data was analyzed using two types of analysis, namely descriptive analysis and SEM analysis. The results of the analysis confirm that (1) the principal's transformational leadership directly influences work motivation; (2) the principal's transformational leadership directly influences the decline in teacher performance; (3) work motivation has a direct effect on teacher performance; (4) the indirect influence of the principal's transformational leadership on teacher performance is mediated by work motivation. The probability value obtained is 0.007 ≤ 0.05. This means that every increase in the principal's transformational leadership will have an indirect impact on increasing teacher performance with the help of mediation in the form of work motivation.